The Probable Association between Blood Groups and Prognosis of COVID-19 - Maryam Nasiri; Javad Khodadadi; Zahra Hajrezaei; Negar Bizhani (Tehran University of Medical Sciences, 2021)
Background: We aimed to verify the association between blood group systems and prognosis of SARS-Cov-2 disease. Methods: In this cross-sectional study, 329 patients infected with SARS-Cov-2 diagnosed based on their COVID-19 RT-PCR results and chest CT scans, were enrolled in the study. These patients were admitted to Kamkar Arab Nia Hospital, Qom, Iran from March to June 2020. Their blood groups and RH were determined, and demographic characteristics and clinical signs of patients were recorded. The patients' temperature and peripheral capillary oxygen saturation levels (SpO2) were measured. Finally, the duration of hospitalization, intubation, and death rate were also analyzed. Results: The results of the patients' blood group analysis were as follows: 129(39.2%) patients had A type, 66(20.1%) B type, 21(6.4%) AB type, and 113(34.3%) O type. Of 329 patients, 297 (90.3%) had Rh antigen. The dead cases were higher in O blood type at 13 cases (11.5%). Considering the positive and negative rhesus antigen, 31 (10.4%) and 1 (3.1%) were dead respectively, but the difference was not statically significant. As for the A group, the mean of admission duration (8.4±6.1 days) was not significantly different from the B group (8.8 ±7.2 days). AB group with a mean (7.4 ±4.4 days) was not significantly different from the O group (7.8 ± 5.4 days). There was no significant difference in the duration of hospitalization in RH patients, positive or negative. B blood group showed a significant association with the time interval to return to normal oxygen levels. Conclusion: Blood type was not associated with COVID-19 death rate, nor was it associated with admission duration. B blood group showed a significant association with the time interval to return to normal oxygen levels.